Impact of Preanalytical Factors on Fecal Immunochemical Tests: Need for New Strategies in Comparison of Methods. Issue 3 (July 2015) - Rubeca, Tiziana; Cellai, Filippo; Confortini, Massimo; Fraser, Callum G.; Rapi, Stefano
Background: Harmonization of fecal immunochemical tests for hemoglobin (FIT-Hb) is crucial to compare clinical outcomes in screening programs. The lack of reference materials and standard procedures does not allow the use of usual protocols to compare methods. We propose 2 protocols, based on artificial biological samples (ABS), to discriminate preanalytical and analytical variation and investigate clinical performances. The protocols were used to compare 2 FIT systems available on European markets: the OC-Sensor Diana (Eiken, Tokyo, Japan) and HM-JACKarc (Kyowa-Medex, Tokyo, Japan). Methods: ABS were obtained adding Hb to Hb-free feces. In the first procedure, 35 ABS were collected for each collection device and analyzed on both systems. In the second, 188 ABS (106 positive and 82 negative) were collected and tested on the specific systems. Passing-Bablock (PB), Pearson's correlation coefficients (R) and Bland-Altman difference analysis were used to compare data. Results: PB, R and mean standard errors for Bland-Altman analysis (Diana vs. Arc) results were 0.93x-0.56: R = 0.97 and 19%; and 1.09x + 5.60: R = 0.96 and −18%; for Diana and Arc devices, respectively. No correlations and no difference in positive/negative assessment were observed with the second protocol. Conclusions: A good correlation was observed in comparing data generated using collection devices on the 2 systems. Manufacturers have developed different sample collection procedures for feces: therefore, data from different systems cannot easily be compared. Adoption of protocols to discriminate preanalytical and analytical variation would be a significant contribution to harmonization of FIT, facilitating data comparison and information acquisition for sample collection strategy and effect of buffers on systems.